(untitled) (Journal of International Studies, 2024)
The practice of the apartheid system in South Africa has been widely condemned for perpetuating enduring socio-economic inequality and for its detrimental impacts on the lives of millions of citizens. While many studies have strongly affirmed this assertion, socio-economic inequality continues to arguably engender a long-lasting struggle among the black and colored communities in post-apartheid South Africa. This places a burden on the country’s successive governments to implement long-term policies that can rectify the plight of the people. Consequently, the adoption of the Millennium Development Goals (MDGs) in 2000 becomes an important reference tool for the African National Congress (ANC)-dominated government, which has initiated and implemented policies to combat inequality in the post-apartheid era. This study examines the roles and measures taken by the ANC government to address racially discriminated economic and social inequality within the framework of the MDGs. Using qualitative research methods, the study explores the background framework of the MDGs and analyzes socio-economic measures implemented by successive ANC governments between 2000 and 2015, focusing on areas such as education, poverty eradication, and healthcare. Primary and secondary sources are utilized to provide insights and support the analysis. The findings reveal that the ANC-dominated government effectively incorporated the frameworks of the MDGs into its formulation and execution of policy measures to eradicate social inequality in South Africa. The study concludes that the effective implementation of these measures has yielded considerable progress, effectively addressing multifaceted issues such as poverty, healthcare, education, and unemployment. This conclusion aligns with the official South African MDG report, which unequivocally highlights the several achievements of MDG targets through policy implementation from 2000 to 2015.